Song as Matrix of Parrēsia: Mtukudzi and the Quest for Truth and Democratic Ethos in Society - Javangwe, Tasiyana D. (Palgrave Macmillan, Cham, 2022)
The intrinsic ethical value of Oliver Mtukudzi’s songs has arguably made him a musical virtuoso globally. His songs are not only philosophically nuanced in their quest for moral rectitude, but also deploy the quality of “free-spokeness” in chastising perceived wrong-doing in society. This chapter seeks to argue that such a quality, beyond the Shona cultural concept of ‘husahwira’, aspires toward the notion of parrēsia. Parrēsia is an ancient Greek notion that “means ‘free-spokeness’, that designates qualities of virtue, duty, and technique in the person who spiritually directs others and helps them to constitute their relationship to self” (Foucault, M., The Government of Self and Others. New York: Palgrave Macmillan, 2010: 43). The person endowed with this vocation, the parrhesiast, has free courage that binds them to the act of telling the truth, regardless of how they open themselves to unspecified risk, which risk does obtain more in politically contested contexts of the nation than in the culturally sanctioned space of the Shona practice of ‘husahwira’.